The Adapting Mind in the Genomic Era - Fieder, Martin; Huber, Susanne (Frontiers in Psychology, 2016)
Genomics and molecular biology has added substantial methods and knowledge to nearly all fields of biology and medicine. In this review we try to demonstrate how genomics and molecular biology is also on the way to have a profound impact on behavioral anthropology, evolutionary psychology, evolutionary sociology and bio-sociology. We propose that particularly studies on “selection and adaptation” will be influenced profoundly by genomics, for instance via identification of the partially genetic basis of human behavior by “candidate gene studies” and by “genome wide association studies”. In addition, epigenetics will lead to a deeper study of the interaction of the genetic basis of a behavior and its environmental regulation. We argue that the “genomic revolution” is much more than merely a new methodological approach, but will change our concepts of human behavior and its development in the evolution of homo.